The Influence of Brand Image, Product Quality, and Price on Purchase Decisions and Repurchase Intention - Amalia, Adella; Waluyo, Minto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Based on data from one of the best e-commerce in Indonesia, sales of flagship smartphones with a price range of 15-18 million rupiah. This study aims to analyze the effect of brand image, product quality, and price on purchasing decisions and repurchase intentions on iPhone smartphones (studies on users of iPhone 14 in Indonesia). This study uses sampling data. In this research study, 20 indicators were used, and based on the Maximum Likelihood (ML) technique, the number of samples that had to be fulfilled was 5 x n(indicators) = 100 pieces. The hypothesis was tested using the Structural Equation Model (SEM) method using AMOS 22 software. The results of this hypothesis test will be followed by using SOAR analysis to determine marketing strategies. This study shows that brand image has a significant effect on purchasing decisions, price has a significant positive impact on buying decisions, and buying decisions have a significant positive effect on repurchasing intention of the iPhone 14 smartphone. So for the model equation, the relationship between exogenous variables and endogenous variables Y2 = 0.262 X1 + 0.413 X3 + Z4.